Synthesis and Characterization of Bioglass 45S Doped with Ag - Bui, Xuan Vuong (H. : ĐHQGHN, 2018)
The bioglass 45S doped with Ag (45S-Ag) was successful synthesized by melting method. The influence of doping Ag on the glass matrix was highlighted by DTA method. XRD analysis confirmed the amorphous structure of synthetic glass. The presence of Ag element was controled by EDX analysis. ‘‘In vitro’’ of synthesized glass was effectuated by soaking of glass powder in SBF solution. EDX result indicated that silver was released when immersing derivative bioglass in SBF solution and silver is an antibacterial agent. XRD and SEM confirmed the bioactivity of glass 45S-Ag by the apatite formation on its surface.